ENRICHING STUDENTS’ VOCABULARY BY USING CHARADE GAME AT PRE-INTERMEDIATE LEVEL - Dwi Megista Putri; Asma Alhusna (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2021)
The study aims to improve English speaking skills with vocabulary mastery through charade game techniques. This research uses library research methods. The biggest problem of today's students lies in mastery of the vocabulary itself. Therefore, teaching staff are required to be able to continue to create ways or techniques of learning in the classroom that can lead students to master english vocabulary more. This game indirectly helps to improve the vocabulary of students. In this game words will be demonstrated with gestures so that students are able to express words with movement. This technique also helps students to be more active in the classroom and motivates students due to the presence of competence in the game. Charade games also help students understand reading texts because vocabulary is difficult to understand first.